PEMBUATAN SURFAKTAN BERBAHAN DASAR MINYAK BIJI KETAPANG Terminalia catappa DENGAN TRIETANOLAMINA - Ravensca, Irene; Saleh, Chairul; Daniel, Daniel (JURNAL ATOMIK, 2017)
Research synthesis esteramin with cattapa seed oils (Terminalia cattapa) has been done through a transesterification reaction. The synthesis process was conducted on the extraction, esterification and transesterification. The results showed cattapa seed oil content of 51.9%, the acid value of 7.559 mg KOH / g and ALB levels of 3.4496%. The composition of the oil determined using GC-MS. GC-MS analysis of the composition of the most dominant oil is oleic acid amounted to 34.86%. Esterification process in the formation of methyl esters can be known ALB decreased to 0.7%. Methyl esters are reacted with triethanolamine through a transesterification reaction. The results showed esteramin water surface tension value of 34.947 dyne / cm, the HLB value of 5.25 is included in the water in oil emulsifiers scale and on a TLC plate there are two stains.